2015
DOI: 10.1016/j.geotexmem.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of discrete fibre reinforcement on the uniaxial compression response and seismic wave velocity of a cement-stabilised sandy-clay

Abstract: a b s t r a c tA sandy clay from the northeast region of Portugal has been reinforced with polypropylene fibres and cement, and seismic wave velocity measurements and uniaxial compression strength tests were performed. Results showed that the fibre induce variations on the wave's velocity that cannot be related to real changes in the material stiffness. Therefore, care should be used when using this technique in fibre reinforced soils. The addition of fibres resulted in an increase of compression strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 37 publications
2
30
2
2
Order By: Relevance
“…The results also indicated that the relative benefit of fibers to enhance the UCS of the clay soils is largely dependent on initial dry unit weight and water content of the soil. Cristelo et al [61] studied the performance of fiber reinforced clayey soil. They found that the excessively compressible clayey soil reinforced with randomly mixed fibers, resulted in higher ultimate bearing capacity, and lesser settlement at the ultimate load.…”
Section: Soil Stabilization Using Fibersmentioning
confidence: 99%
“…The results also indicated that the relative benefit of fibers to enhance the UCS of the clay soils is largely dependent on initial dry unit weight and water content of the soil. Cristelo et al [61] studied the performance of fiber reinforced clayey soil. They found that the excessively compressible clayey soil reinforced with randomly mixed fibers, resulted in higher ultimate bearing capacity, and lesser settlement at the ultimate load.…”
Section: Soil Stabilization Using Fibersmentioning
confidence: 99%
“…Fatahi et al (2013) carried out bender element tests on 126 cylindrical samples of cement-treated kaolinite and bentonite clays with various cement and fiber (polypropylene and recycled carpet) contents to discern the relationship between fiber and cement content and the small-strain mechanical properties, including the shear wave velocity and maximum small-strain shear modulus of treated soils. Cristelo et al (2015) carried out ultrasonic wave and uniaxial compression tests to measure P-wave velocity and compression strength in cement-stabilised sandyeclay reinforced with polypropylene fiber. Tests results indicated that stiffness and compression strength of sandy soil, increases with cement and fiber content.…”
Section: Fiber-reinforced Soilmentioning
confidence: 99%
“…Cristelo N et al, Influence of fibre reinforcement on the post-cracking behaviour of a cement-stabilised sandy-clay subjected to indirect tensile stress, Construction and Building Materials, Elsevier, 138: 163-173, 2017. Doi: 10.1016/j.conbuildmat.2017.02.010 5 Additional geotechnical and microstructural details, as well as a more thorough explanation on 95 the preparation of the fibres, can be found in (Cristelo et al, 2015). The following is the essential 96 information presented in the aforementioned paper.…”
mentioning
confidence: 99%